(N,N′-Diisopropyldithiocarbamato)triphenyltin(IV): crystal structure, Hirshfeld surface analysis and computational study - Farah N. H.,; Normah Awang,; Nurul Farahana Kamaludin,; Jotani, Mukesh M.; Tiekink, Edward R. T. * (International Union of Crystallography, 2019)
The crystal and molecular structures of the title triorganotin dithiocarbamate, [Sn(C6H5)3(C7H14NS2)], are described. The molecular geometry about the metal atom is highly distorted being based on a C3S tetrahedron as the dithiocarbamate ligand is asymmetrically chelating to the tin centre. The close approach of the second thione-S atom [SnS = 2.9264 (4) A˚ ] is largely responsible for the distortion. The molecular packing is almost devoid of directional interactions with only weak phenyl-C—HC(phenyl) interactions, leading to centrosymmetric dimeric aggregates, being noted. An analysis of the calculated Hirshfeld surface points to the significance of HH contacts, which contribute 66.6% of all contacts to the surface, with CH/HC [26.8%] and SH/HH [6.6%] contacts making up the balance.